DIURETIC DOPPLER ULTRASOUND FOR EVALUATING OBSTRUCTED AND NON-OBSTRUCTED KIDNEY - Fajrial, Ahmad Fajrial; Soebadi, Doddy M; Djojodimedjo, Tarmono; S, Muhammad Yamin; Pudjirahardjo, Widodo (Indonesian Urological Association, 2013)
Objective: The objective of this study was to evaluate the implementation of diuretic Doppler Ultrasound (DDU) to differentiate the obstructed and non-obstructed kidney. Material & Method: From 28 patients, we gathered data of 48 kidneys in accordance with the inclusion criteria. We evaluated the Doppler Ultrasound Resistive Index (RI) before and after administration of diuretic, using the renogram as the comparison. The result of renogram was categorized into total obstruction (n = 19), partial obstruction (n = 18), and non-obstructive dilatation (n = 3). The statistical analysis was performed using Anova test followed by Tukey HSD test. We also performed diagnostic test, the total and partial obstruction were categorized within obstructed group (n = 37) whereas normal and non-obstructed dilated kidney categorized as non-obstructed group (n = 11). Results: Average change of RI (ΔRI) was 0,542 ± 0,0457 for total obstruction, 0,0428 ± 0,0439 for partial obstruction, 0,0275 ± 0,0392 for normal kidney, -0,0300 ± 0,0361 for non obstructed dilated kidney. The result of normality and homogeneity test indicated the data were normally distributed. One-way Anova test revealed significant differences of ΔRI between groups. The subsequent Tukey HSD test indicated that there were significant differences in total and partial obstruction groups, compared to non-obstructive dilated kidney group. Based on ΔRI cut-off point (0,035) the diagnostic characteristics were 88,5% sensitivity and 72,3% specificity. Conclusion: RI of Diuretic Doppler Ultrasound is a valuable examination to evaluate obstructed and non-obstructed kidney. The cut-off point of 0,035 indicated probability of obstructive kidney. Keywords: Resistive index, renogram, obstructive kidney, non-obstructive kidney.